Coral reefs - Gibbons, Gail. (New York : Holiday House, 2007)
Marine biologists believe coral reefs existed 400 million years ago, when dinosaurs roamed the earth. Today this active environment is home to about 20,000 kinds of brilliantly coloured corals, plants, and animals-more sea creatures than are found anywhere else in the world. The Great Barrier Reef in Australia is so large that astronauts can see it from outer space...
Q
b
b
Keywords: Coral reef ecology -- Juvenile literature; Coral reefs and islands -- Juvenile literature